Evaluation of Vitamin E Isoforms in Placental Tissue and Their Relationship with Maternal Dietary Intake and Plasma Concentrations in Mother-Infant Dyads - Ishani Jhamb; Alyssa Freeman; Michelle R. Lotfi; Matthew VanOrmer; Corrine Hanson; Ann Anderson-Berry; Melissa Thoene (MDPI AG, 2023)
α-tocopherol is a vitamin E isoform with potent antioxidant activity, while the γ-tocopherol isoform of vitamin E exerts more pro-inflammatory effects. In maternal-fetal environments, increased plasma α-tocopherol concentrations are associated with positive birth outcomes, while higher γ-tocopherol concentrations are linked with negative pregnancy outcomes. However, little is known about tocopherol concentrations in placental tissue and their role in modulating placental oxidative stress, a process that is implicated in many complications of pregnancy. The objectives of this research are to evaluate the concentrations of α- and γ-tocopherol in placental tissue and assess relationships with maternal and umbilical cord plasma concentrations. A total of 82 mother-infant dyads were enrolled at the time of delivery, and maternal and umbilical cord blood samples and placenta samples were collected. α- and γ-tocopherol concentrations in these samples were analyzed by high-performance liquid chromatography (HPLC). γ-tocopherol concentrations demonstrated significant, positive correlations among all sample types (p-values < 0.001). Placental tissue had a significantly lower ratio of α:γ-tocopherol concentrations when compared to maternal plasma and umbilical cord plasma (2.9 vs. 9.9 vs. 13.2, respectively; p < 0.001). Additional research should explore possible mechanisms for tocopherol storage and transfer in placental tissue and assess relationships between placental tocopherol concentrations and measures of maternal-fetal oxidative stress and clinical outcomes of pregnancy.